Characterization of in vitro metabolites of luotonin A in human liver microsomes using electrospray/tandem mass spectrometry - Lee, Sangkyu; Lee, Jaeick; Jahng, Yurngdong; Jeong, Tae Cheon; Kim, Dong Hyun (INFORMA HEALTHCARE, 2013)
1. The pharmacological activity of luotonin A varies, depending on the type of functional group and the site of derivatization. To understand the in vivo efficacy of luotonin A, the in vitro metabolism of luotonin A was investigated in human liver microsomes and recombinant cDNA-expressed cytochromeP450 (CYP). 2. Incubation of luotonin A with pooled human liver microsomes in the presence of NADPH-generating system resulted in the formation of four metabolites and the structures of each metabolite were tentatively characterized on the basis of electrospray tandem mass spectra. 3. The main metabolic pathway of luotonin A in human liver microsomes was hydroxylation, resulting in the generation of two mono-hydroxyl metabolites (M1 and M2) and two di-hydroxyl metabolites (M3 and M4). CYP1A2 was primarily involved in hydroxylation of the quinolone moiety (M1 and M3), while CYP3A4 was mainly responsible for hydroxylation of the quinazoline moiety of luotonin A (M2 and M4) in human liver microsomes.
Keywords: A DERIVATIVES; RUTAECARPINE; ALKALOIDS; TRYPTANTHRIN; RING